Pro-environmental Behavior of University Students: Influence of Cultural Differences - Tezel, Ecem; Ugural, Mehmet; Giritli, Heyecan (European Journal of Sustainable Development, 2018)
Responsible Consumption and Production, among the Sustainable Development Goals, indicates that humans should be aware of environmental problems which are to some extent, direct or indirect consequences of their behaviors. This indicates that the question of what shapes pro-environmental behavior (PEB) is difficult to understand. There has been an increasing concern towards individuals’ PEBs both at home and in the workplace. However, although some studies have shown significant concern-behavior relationship, others have revealed that environmental concern (EC) fails to predict PEB. Thus, whether individuals with higher levels of environmental concern perform more PEB has not received robust empirical support. Drawing on the corresponding literature, concern-behavior gap can be explained by the concept of cultural environmental biases. This study aims to test how cultural biases shape PEB. Following the model proposal which explores the effect of cultural biases on EC and PEB, a 42-item questionnaire has been developed and applied with the university students as they are expected to be the most informed and aware people about environmental issues. The findings are expected to deepen the understanding of concern-behavior relationship and cultural environmental biases as well as provide new insights for sustainable development practices. Keywords: pro-environmental behavior, environmental concern, cultural environmental biases, sustainable development goals